Risk factors associate with overweight and obesity in adolescents - Carmen Emilia Guerra Cabrera; Jesús Vila Díaz; Juan José Apolinaire Pennini; Ailyn del Carmen Cabrera Romero; Inti Santana Carballosa; Pilar Maritza Almaguer Sabina (Medisur)
Background: Overweight and obesity have high prevalence among children and adolescent in industrialized countries and, since the 90´s, there is also an increase in developing counties. Objective: To determine the relevant risk factors associated with overweight in children. Methods: We designed a case-control, analytical, observational, retrospective research including 50 school age adolescents assessed after their body mass index as obese and overweight (cases) and 50 adolescents with normal weight (controls), between the ages of 10 and 12 years from four primary schools belonging to Health Area III of Cienfuegos municipality. The studied variables were: kind of feeding during the first months, hours of physical activity, sport practice, hours of sedentary activity, personal pathological history, kind of food and consumption frequency. Results: The overweight adolescents presented higher incidence of mixed kinds of feeding during the first months, little daily physical activity, little sport practice, high average of daily hours in front of the TV or PC, higher incidence of family history of obesity and nutritional patter based on cereals, milk, sugar, beans, and low consumption of fruits, fish and vegetables. Conclusion: We confirmed the hypothesis that children with more incidences of the selected risk factors are more likely to develop overweight and obesity.